Badiou reframed : interpreting key thinkers for the arts - Ling, Alex (London : I.B. Tauris, 2016)
"He has been regarded with suspicion by some, as an anti-postmodernist who dared to write about unfashionable concepts such as truth and meaning. But in recent years, the philosopher Alain Badiou has risen in prominence, pioneering new ways to produce, conceptualise and discover art. Badiou Reframed is an original book about an original thinker which applies - for the first time - Badiou's philosophy to the visual arts. The six central concepts of this philosophy - 'being and appearing', 'event and subject' and 'truth and ethics' - are elucidated through detailed analysis of a range of visual artworks, including Marcel Duchamp's readymades, the abstract paintings of Kazimir Malevich and Mark Rothko, Banksy's contemporary street art, the sculpture of Alberto Giacometti, Stephane Mallarme's visual poetry and Victor Fleming's classic film The Wizard of Oz. In focusing on Badiou's critical relationship with the visual arts, Alex Ling reinterprets and represents not only the man, but art itself."--Bloomsbury Publishing.
List of illustrations Note on the use of mathematics in the text Introduction. First impressions Part One. Being and appearing Chapter 1. Unframing, enframing, reframing Chapter 2. Philosophy under condition Part Two. Event and subject Chapter 3. The shock of the new Chapter 4. The subject of art Part Three. Truth and ethics Chapter 5. From here to eternity Chapter 6. Keeping the faith Conclusion. Badiou reframed Notes Bibliography Index.
Includes bibliographical references and index.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Also issued in print.
Electronic reproduction.
Keywords: Badiou, Alain; Philosophers -- France -- Biography; Art -- Philosophy; Western philosophy, from c 1900 -.